Labeling methods for association rule clustering - De Carvalho, Veronica Oliveira [UNESP]; Biondi, Daniel Savoia [UNESP]; Dos Santos, Fabiano Fernandes; Rezende, Solange Oliveira (INSTICC, 2012)
Although association mining has been highlighted in the last years, the huge number of rules that are generated hamper its use. To overcome this problem, many post-processing approaches were suggested, such as clustering, which organizes the rules in groups that contain, somehow, similar knowledge. Nevertheless, clustering can aid the user only if good descriptors be associated with each group. This is a relevant issue, since the labels will provide to the user a view of the topics to be explored, helping to guide its search. This is interesting, for example, when the user doesn't have, a priori, an idea where to start. Thus, the analysis of different labeling methods for association rule clustering is important. Considering the exposed arguments, this paper analyzes some labeling methods through two measures that are proposed. One of them, Precision, measures how much the methods can find labels that represent as accurately as possible the rules contained in its group and Repetition Frequency determines how the labels are distributed along the clusters. As a result, it was possible to identify the methods and the domain organizations with the best performances that can be applied in clusters of association rules.
Keywords: Association rules; Clustering; Labeling methods; Post-processing; Association mining; Descriptors; Post processing; Repetition frequency; Information systems